Antiproliferative activity and energy calculations of a new triterpene isolated from the palm tree Acrocomia totai. Issue 22 (18th November 2021) - Souza, Gredson Keiff; Kischkel, Brenda; Freitas, Camila Fabiano; Negri, Melyssa; Back, Davi; Johann, Gracielle; Hioka, Noboru; Schuquel, Ivânia Terezinha Albrecht; Santin, Silvana Maria Oliveira; Pomini, Armando Mateus
Abstract: Acrocomia totai Mart ( Arecaceae ) is a palm tree native to South America, widely studied for biodiesel production. The aim of this work was to perform the first phytochemical study of A. totai leaves, as well as to do biological assays against human cancer cell lines. A new triterpene of the hopane class named totaiol (1), three known triterpenes (2–4), and two phytosteroids (5–6) were identified. The new natural product was characterized using 1 D and 2 D NMR, single crystal X-ray diffraction analises, and high resolution mass spectrometry. The intercontacts in the crystal packing were also analised. Complete stereochemical characterization of compound 1 revealed an unusual positioning pattern for methyl and isopropenyl groups in the polycyclic skeleton. Compounds 1–5 were evaluated for the first time in antiproliferative assays against Ca Ski, MCF-7 and MCF-10 cells. The new natural product was active against Ca Ski cells with IC50 ≤ 6.25 µg mL −1 . Graphical Abstract: